2014
DOI: 10.1016/j.rgg.2014.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Early Cretaceous granitoids of the Samarka terrane (Sikhote-Alin’): geochemistry and sources of melts

Abstract: We present new data on the geologic position, composition, and isotope characteristics of the Early Cretaceous granitoids of the Samarka terrane, Sikhote-Alin’, formed on a transform continental margin. Geological and geochronological data show that these granitoids were generated at two stages of magmatism: in the first half (Hauterivian–Barremian, 130–123 Ma) and second half (Albian–Cenomanian, 110–98 Ma) of the Early Cretaceous. Granitoids of the first stage form an autonomous (free of basic precursors) uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Our planet released 'escaped vapor' at the beginning of its seasonal contraction. Formation of the colossal petroleum reserves sourced by the Aptian-Turonian strata (about 1/3 of all the The Far Eastern Russia changes are presented after Baskina et al, 2006;Berdnikov and Karsakov, 1999;Chashchin et al, 2014;Faure et al, 1994;Geological …, 2014;Golozoubov et al, 2006;Jahn et al, 2015;Krasilov, 1967;Kruk et al, 2014;Markevich et al, 2000;Markevich, 1995;Oleynikov et al, 1990;Podolyan et al, 1997;Prikhod'ko et al, 2009;Sakhno et al, 2011;Sharudo, 1972;Simanenko et al, 2006;Volynets, 2009;Wu et al, 2017. world's oil and gas reserves) was one of the great economic results of this escape (Klemme and Ulmishek, 1991;Larson, 1991). Biogenic sedimentation, which predominated in the Early Mesozoic oceans, started being replaced by terrigenous deposits at about 120 Ma, when oceanic red clays appeared (Hu et al, 2012;and references therein).…”
Section: Phanerozoic and Late Proterozoicmentioning
confidence: 99%
See 2 more Smart Citations
“…Our planet released 'escaped vapor' at the beginning of its seasonal contraction. Formation of the colossal petroleum reserves sourced by the Aptian-Turonian strata (about 1/3 of all the The Far Eastern Russia changes are presented after Baskina et al, 2006;Berdnikov and Karsakov, 1999;Chashchin et al, 2014;Faure et al, 1994;Geological …, 2014;Golozoubov et al, 2006;Jahn et al, 2015;Krasilov, 1967;Kruk et al, 2014;Markevich et al, 2000;Markevich, 1995;Oleynikov et al, 1990;Podolyan et al, 1997;Prikhod'ko et al, 2009;Sakhno et al, 2011;Sharudo, 1972;Simanenko et al, 2006;Volynets, 2009;Wu et al, 2017. world's oil and gas reserves) was one of the great economic results of this escape (Klemme and Ulmishek, 1991;Larson, 1991). Biogenic sedimentation, which predominated in the Early Mesozoic oceans, started being replaced by terrigenous deposits at about 120 Ma, when oceanic red clays appeared (Hu et al, 2012;and references therein).…”
Section: Phanerozoic and Late Proterozoicmentioning
confidence: 99%
“…The major orogenic phase, that finally consolidated the Sikhote-Alin terranes, happened during the late Aptianearly Albian (115-110 Ma). This event is reflected in isotopic dating of mica from the Anyuy metamorphic dome (Faure et al, 1995;Kruk et al, 2014) and hydrocarbon metasomatic rocks from the Dal'negorsk ore district (Baskina et al, 2006), that are close to the mid-Cretaceous plate reorganization in both the Pacific and more globally (Matthews et al, 2012;Vaughan, 1995).…”
Section: Southern Far East Russia and Adjacent Regionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Sikhote‐Alin terranes were accreted one by one to the eastern margin of the Bureya‐Jiamusi‐Khanka Block before the Late Cretaceous (Golozoubov, Markevich, & Bugdaeva, ; Khanchuk et al, , ). Cretaceous to Cenozoic magmatism is widespread in the whole area, which is mainly recorded by plutons and their extrusive equivalents, in which most of them are rhyolitic to andesitic (Jahn et al, ; Kruk et al, ; Figure ). The known zircon U–Pb ages of the magmatic rocks range from the Early Cretaceous in the west to Paleogene in the southeast (Jahn et al, ; Khanchuk et al, ; Tang et al, ).…”
Section: Geological Backgroundmentioning
confidence: 99%
“…For instance, previous studies showed that the volcanic rocks with ages of 135 to 110 Ma were mainly located in the western NE China (mainly in the Great Xing'an Range and Songliao Basin). However, recent studies reveal that the arc‐related granitoids in the western the Sikhote‐Alin area also have ages from 135 to 110 Ma (Cheng et al, ; Jahn et al, ; Kruk et al, ). Thus, the migration of magmatism in NE Asia should include both the continental arc and back‐arc areas, like suggested by the third model (M. Sun et al, ).…”
Section: Tectonic Implicationsmentioning
confidence: 99%